BRAF Mutation Is Associated with Improved Local Control of Melanoma Brain Metastases Treated with Gamma Knife Radiosurgery - Gallaher, Ian S.; Watanabe, Yoichi; DeFor, Todd E.; Dusenbery, Kathryn E.; Lee, Chung K.; Hunt, Matthew A.; Lin, Hong-Yiou; Yuan, Jianling (Frontiers in Oncology, 2016)
Objectives: Evidence has implicated a possible role of tumor mutation status on local control (LC) with radiotherapy. BRAF is a proto-oncogene that is mutated in approximately 50% of patients with melanoma. We sought to analyze the influence of BRAF status on LC of melanoma brain metastases following Gamma Knife radiosurgery (GK). Methods: Among 125 patients treated with GK for melanoma brain metastases at our institution between 2006 and 2015, we identified 19 patients with 69 evaluable metastases whose BRAF mutation status was known and follow-up imaging was available. LC of individual metastases was compared based on BRAF mutation status using statistical techniques to control for measurements of multiple metastases within each patient. CNS progression was defined as either local failure or development of new lesions. Results: Of the 69 metastases, BRAF was mutated in 30, and wild-type in 39. With a median follow-up of 30 months for all patients and a median follow-up of 5.5 months for treated lesions, one-year LC was significantly better among metastases with mutated vs. wild-type BRAF (69% vs. 34%, RR = 0.3, 95% CI = 0.1-0.7, p = 0.01). BRAF mutation was found to be a significant predictor of LC after SRS in both univariate (RR=0.3, [95% CI 0.1-0.7, p = 0.01]) and multivariate (RR=0.2, [95% CI 0.1-0.7, p = 0.01]) analyses. There was also a trend towards improved CNS progression free survival (PFS) at one year (26% vs. 0%, p=0.06), favoring BRAF-mutated patients. Conclusions: In this retrospective study, melanoma brain metastases treated with GK had significantly improved local control for patients with BRAF mutation vs. wild-type. Our data suggest that BRAF mutation may sensitize tumors to radiosurgery, and that BRAF wild-type tumors may be more radioresistant. Results: Of the 69 metastases, BRAF was mutated in 30, and wild-type in 39. With a median follow-up of 30 months for all patients and a median follow-up of 5.5 months for treated lesions, one-year LC was significantly better among metastases with mutated vs. wild-type BRAF (69% vs. 34%, RR = 0.3, 95% CI = 0.1-0.7, p = 0.01). There was also a trend towards improved CNS progression.